Induction of labour in mid-trimester pregnancy using double-balloon catheter placement within 12 h versus within 12-24 h - Jing Peng; Ruobing Li; Shuguo Du; Heng Yin; Min Li; Xuan Zheng; Shiyao Wu; Yun Zhao (BMC, 2021)
Abstract Background This study aims to evaluate the efficacy and safety of the induction of labour in mid-trimester pregnancy using a double-balloon catheter (DBC) within 12 h versus within 12-24 h. Methods In this retrospective study, a total of 58 pregnant women at 14 + 0 weeks to 27 + 6 weeks of gestation were enrolled as research subjects, and they underwent the intended termination of pregnancy at our birth centre from January 1, 2017, to June 31, 2019. Based on the duration of DBC, the patients were divided into two groups, namely, the DBC group within 12 h and the DBC group within 12-24 h. Results All 58 cases were successful vaginal deliveries, and no one chose to undergo caesarean section. The success rate of induction (successful abortion of the foetus and placenta without the implementation of dilation and evacuation) was higher in the DBC group within 12-24 h (96.3%, 29/31) than in the DBC group within 12 h (71.0%, 18/27) (p < 0.05). Additionally, the time from DBC removal to delivery in the DBC group within 12-24 h was significantly shorter than that in the DBC group within 12 h (3.0 h versus 17.8 h) (p < 0.05), and the degree of cervical dilation after DBC removal in the DBC group within 12-24 h was larger than that in the DBC group within 12 h (p < 0.05). Conclusion In the clinic, the placement time of DBC generally lasts for approximately 12 h. However, considering that the cervical condition is immature in the mid-trimester, properly extending the placement time of DBC to 24 h will benefit cervical ripening and reduce the chance of dilation and evacuation.